Theoretically predicting the feasibility of highly-fluorinated ethers as promising diluents for non-flammable concentrated electrolytes - Bouibes, Amine; Saha, Soumen; Nagaoka, Masataka (Scientific reports, 2020)
The practical application of nonflammable highly salt-concentrated (HC) electrolyte is strongly desired for safe Li-ion batteries. Not only experimentalists but also theoreticians are extensively focusing on the dilution approach to address the limitations of HC electrolyte such as low ionic conductivity and high viscosity. This study suggests promising highly-fluorinated ethers to dilute the HC electrolyte based on non-flammable trimethyl phosphate (TMP) solvent. According to the quantum mechanical and molecular dynamics calculations, the fluorinated ether diluents showed a miscibility behavior in HC TMP-based electrolyte. While such miscibility behavior of the diluent with TMP solvent has been significantly enhanced by increasing its degree of fluorination, i.e., the “fluorous effect”, it is remarkable that the self-diffusion constant of Li + and the ionic conductivity should be significantly improved by dilution with bis(1,1,2,2-tetrafluoro ethyl) ether (B2E) and bis(pentafluoro ethyl) ether (BPE) compared to other common hydrofluoroether diluents. In addition, the fluorinated-ether diluents have high ability to form a localized-concentrated electrolyte in HC TMP-based solution, leading to high expectation for the formation of a stable and a compact inorganic SEI film.